2013
DOI: 10.1182/blood-2012-06-439786
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cell homeostasis in mice is dependent on mTORC1 but not mTORC2 function

Abstract: Key Points• mTORC1 activity in DCs by conditional deletion of Raptor leads to a progressive loss of LCs in the skin of mice.• mTORC1 but not mTORC2 is required for epidermal LC homeostasis.The PI3K/Akt/mTOR pathway has emerged as a critical regulator of dendritic cell (DC) development and function. The kinase mTOR is found in 2 distinct complexes, mTORC1 and mTORC2. In this study, we show that mTORC1 but not mTORC2 is required for epidermal Langerhans cell (LC) homeostasis. Although the initial seeding of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 52 publications
4
43
1
1
Order By: Relevance
“…Interestingly, a recent report showed that raptor-mediated disruption of mTORC1 signaling critically affects LC homeostasis. 39 ERK as well as mTOR signaling are known to mediate/regulate fundamental cellular processes like growth factor signaling, 12 cell growth and proliferation, 12,40 as well as the nutritional status of the cell. 9,10 This may connect cell ontogeny and mTOR/ERK signaling in that less mTORC1/ERK signaling (as shown for LCs) results in less proliferation and less inhibition (ie, promotion) of catabolic 40 processes such as apoptosis, as we have established.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent report showed that raptor-mediated disruption of mTORC1 signaling critically affects LC homeostasis. 39 ERK as well as mTOR signaling are known to mediate/regulate fundamental cellular processes like growth factor signaling, 12 cell growth and proliferation, 12,40 as well as the nutritional status of the cell. 9,10 This may connect cell ontogeny and mTOR/ERK signaling in that less mTORC1/ERK signaling (as shown for LCs) results in less proliferation and less inhibition (ie, promotion) of catabolic 40 processes such as apoptosis, as we have established.…”
Section: Discussionmentioning
confidence: 99%
“…Akt1 À/À and Akt2 À/À mice were provided by O. Tschopp (University of Zü rich). ItgaxRictor-Raptor fl/fl mice were provided by T. Broker (Kellersch and Brocker, 2013). All animals were housed in individually ventilated cages under specific-pathogen-free conditions at the ETH Phenomics Facility and used for experiments at between 6 and 14 weeks of age unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, FLT3L-mediated expansion of pre-DCs in the spleen and to a lesser degree in the blood and lung was decreased with Rapamycin ( Figure S5A). In order to more comprehensively address the role of the mTOR pathway in DC development, we analyzed mice deficient in both RAPTOR and RICTOR specifically in DCs (Kellersch and Brocker, 2013). These two proteins are key components of mTORC1 and mTORC2, respectively (Weber and Gutmann, 2012).…”
Section: Mtorc1 and Mtorc2 Control DC Development In An Organ-specifimentioning
confidence: 99%
“…These effects can be inhibited by rapamycin 17 . Moreover, the Cd11c –Cre-mediated deletion of Raptor , which encodes a key component of mTORC1, alters steady-state DC populations, increasing the numbers of splenic cDCs 20 but reducing the numbers of epidermal Langerhans cells 21 . Generally consistent with these findings, the tamoxifen-induced oestrogen receptor–Cre-mediated deletion of floxed Tsc1 (which encodes tuberous sclerosis 1, another negative regulator of mTORC1), results in enhanced outgrowth of DCs from GM-CSF-stimulated bone marrow cultures 22 .…”
Section: Metabolism In Developing and Resting Dcsmentioning
confidence: 99%